Punicalin Alleviates OGD/R-Triggered Cell Injury via TGF-β-Mediated Oxidative Stress and Cell Cycle in Neuroblastoma Cells SH-SY5Y. (12th February 2021) - Yang, Tiansong; Wang, Qingyong; Qu, Yuanyuan; Liu, Yan; Feng, Chuwen; Wang, Yulin; Sun, Weibo; Sun, Zhongren; Zhu, Yulan
Abstract : Purpose . The research aimed to identify the active component from Punica granatum L. to alleviate ischemia/reperfusion injury and clarify the underlying mechanism of the active component alleviating ischemia/reperfusion injury. Materials and Methods . The SH-SY5Y cell model of oxygen-glucose deprivation/reoxygenation (OGD/R) was established to simulate the ischemia/reperfusion injury. According to the strategy of bioassay-guided isolation, the active component of punicalin from Punica granatum L. was identified. Flow cytometry and Western blotting were employed to evaluate the effects of OGD/R and/or punicalin on cell cycle arrest. Immunofluorescence assay was applied to assess the nucleus translocation. The relative content of ROS and GSH and the enzyme activities of CAT and SOD were examined using ELISA. Results . The data of bioassay-guided isolation showed that punicalin from Punica granatum L. could alleviate OGD/R-induced cell injury in SH-SY5Y cells. Flow cytometry analysis and Western blotting for probing the expression of CDK1, p-CDK1, cyclin B1, and p21 revealed that punicalin could relieve OGD/R-induced cell cycle G0/G1 arrest. Additionally, immunofluorescence assay and Western blotting for probing the expression of TGF- β and p-Smad2/p-Smad3 showed that punicalin could relieve the OGD/R-induced TGF- β /Smad pathway. Furthermore, the TGF- β /Smad pathway inhibitor of LY2157299 was employed to confirm that the TGF- β /Smad pathway is crucial to the effect of punicalin. At last, it was indicated that punicalin could relieve OGD/R-induced oxidative stress. Conclusion . Punicalin, an active component from Punica granatum L., was identified as a protective agent to alleviate the OGD/R-induced cell injury, which could exert the protective effect via TGF- β /Smad pathway-regulated oxidative stress and cell cycle arrest in SH-SY5Y cells.